Short Term Organ Culture of Mouse Ovary in the Medium Supplemented with Bone Morphogenetic Protein 15 and Follicle Stimulating Hormone: A Morphological, Hormonal and Molecular Study - M Salehnia; M Pajokh; N Ghorbanmehr (JRI, 2016)
Background: Bone morphogenetic protein 15 (BMP15) is a growth factor derived from oocyte and is essential for in vivo ovarian follicular growth and in this study, its effects on the improvement of growth and development of follicles during in vitro culture of neonatal mouse ovaries was investigated. Methods: Two week old mice were cultured for 7 days in the basic culture media with or without follicle stimulating hormone (FSH) and BMP15 as four experimental groups; FSH-/BMP15-, FSH+/BMP15-, FSH-/BMP15+ and FSH+/BMP15+. The ovarian follicles at different developmental stages in paraffin embedding sections of cultured and non-cultured ovaries were counted and compared. The 17-β estradiol (E2) and progesterone (P4) levels were analyzed in collected culture media. The expression ratio of developmental genes (PCNA, BMPR-IB, BMPR-II, FSH-R, CYP17 and ZP3) to housekeeping gene (GAPDH) was analyzed by real time PCR (RT-PCR) in comparison with non-cultured control ovaries. The data was compared by independent t-test and one-way ANOVA (with Tukey’s Post Hoc test). The p<0.05 was considered significant. Results: The percentage of antral follicles, ovarian size, concentration of E2 and P4 and the expression ratio of PCNA and ZP3 genes in the ovaries cultured in medium supplemented with BMP15 and FSH increased significantly in comparison with other cultured groups (p<0.05). The BMPR-IB, BMPR-II and FSH-R mRNA level was significantly lower (p<0.05) and CYP 17 mRNA level did not change in the FSH+/BMP15+ group than other cultured groups. Conclusion: This study demonstrated a favorable effect of BMP15 in combination with FSH on in vitro development of small size mouse follicles to antral stage.